Viabilidade do processo operacional da Central de Tratamento de Resíduos da Caturrita (CTRC) - Santa Maria, RS - Salamoni, Rafael Hollweg (2008)
This approach identifies some physical characteristics of the residues and the operational procedures converning the destination of these residues at the Central of Residues Treatment of Caturrita (CTRC), located on the city of Santa Maria (RS). The CTRC is composed by unit of selection, unit of compostage and sanitary embarement, wich supports a population of nearly 500.000 habitants, and has a 30 years estimated life-time for the enterprise. It is located in area of 24, 7 hectares, within the Vicinal Road to Santa Maria (Boca do Monte). The enterprise is licensed to daily receive 300t of residues. The physical characteristics and the operational procedures were taken and executed with the residue from the selection unit. It evaluated the specific mass and the operational procedures of compacting, receiving of residues, transport of residues to the landfill place, utilized machines and life-time of the sanitary embarement for the actual operational system and for the operational system that uses a press to compact the residues. Sixteen packs of compact residues using a vertical press. The evaluation results showed a significant operational and economic qualification in the operational system of compacting residues in press. This is due to the fact that the residues were compacted in smell volumes, forming easy operated packs with higher values of specific mass. The compactation of the residue in a vertical press provided an increase in the specific mass and consequently a volumetric reduction of 5, 33 times. These residues were compacted in sunny and rainy days and with presence of organic matter, and for that, the compactitation generated effluent in significant amount, wich any was would be generated in the sanitary embarement. There was no way to set, through the availall data, the days and intervals of peak hours, but it was verified that the amount of processed residues by hour is lawer than to the amount produced with the operational processing of presses of the type MAC 108L/1. The compaction process showed a gain in efficiency in charge of 28.6% and the economy in the consume of diesel of 31,5%. The managing of machinery to compact residues in press demonstrated a reduction in the number of utilized equipments and the life-time of the sanitary sanitary embarement for compacted residues by press would pass from 30 years for 39, 1 years.